Analisis Perbandingan Usaha Tani Tambak Udang di Desa Paluh Manan dan Desa Lama Kecamatan Hamparan Perak Kabupaten Deli Serdang Provinsi Sumatera Utara - M. Dani Habra; Syaad Afifuddin; Rahmanta Ginting; Rahma Sari Siregar (JURNAL AGRICA, 2018)
One of the fishing activity is increased and is relied upon in the future by the Deli Serdang Regency is the brackish water aquaculture, such as shrimp. The land use of shrimp farms can be replace the role of fishing is estimated to have exceeded the allowable catch, especially on the East Coast of Sumatra in the coastal of Deli Serdang Regency. The development of farm land was centered in Hamparan Perak District. There is supported with specific aquatic environment, to be located in the coastal region of Deli Serdang Regency. By the optimal and sustainable management, the potential of pond at Hamparan Perak District is expected to contribute an adequate production in accordance with the carrying capacity of the region . The purpose of the study was to determine the shrimp farm income in Paluh Manan and Lama Villages at Hamparan Perak District, and to find out the feasibility of the shrimp farming in the Paluh Manan and Lama Villages at Hamparan Perak District. This study will be conducted in the Paluh Manan and Lama Villages at Hamparan Perak District for two months from January 2011 to March 2011. Based on the analysis and discussion that has been concluded that: the difference in the average of expansive farm land, number of labor, farming seeding, farming feed, drugs farm, and farm profits. The value of total profit at Lama Village obtained is Rp . 20.574.275 and at Paluh Manan Village is Rp. 13.395.954. From the comparison of the farm income in the shrimp pond at Lama and Paluh Manan Villages, the greater income is the farming at Lama Village. The difference average total farm profits of the shrimp pond at Lama Village and Paluh Manan Village is Rp. 7.178.321. Keywords : farming, food, shrimp